Trianthema decandra L. - An Uncultivated Green Leafy Vegetable - Soujanya, Kanneboina; Kumari, B. Anila; Suneetha, W. Jessi; Jyothsna, E. (Chronicle of Bioresource Management, 2021)
The uncultivated or wild green leafy vegetables refers to those wild plants which are neither cultivated nor domesticated and can be available naturally. Wild edible plants are still eaten by many sections of the population. In addition to being resilient and adaptive, these vegetables also demand low-cost plantation and harvesting. Trianthema decandra is an invasive weed of cultivated fields and wastelands. The whole plant is used to treat various health problems like skin diseases, fever, tooth problems and wound healing. The roots are also used for eye problems like dimness of sight and night blindness, ulcers, itching and bacterial infections. Many evidences demonstrated that medicinal plants have the potential to be used in various complementary, traditional and alternate systems of treatment of human and non-human diseases. To provide more scientific evidence, much research has to be done in this area.